Prevention of dsRNA‐induced interferon signaling by AGO1x is linked to breast cancer cell proliferation. (19th August 2020) - Ghosh, Souvik; Guimaraes, Joao C; Lanzafame, Manuela; Schmidt, Alexander; Syed, Afzal Pasha; Dimitriades, Beatrice; Börsch, Anastasiya; Ghosh, Shreemoyee; Mittal, Nitish; Montavon, Thomas; Correia, Ana Luisa; Danner, Johannes; et al.
Abstract: Translational readthrough, i.e., elongation of polypeptide chains beyond the stop codon, was initially reported for viral RNA, but later found also on eukaryotic transcripts, resulting in proteome diversification and protein‐level modulation. Here, we report that AGO1x, an evolutionarily conserved translational readthrough isoform of Argonaute 1, is generated in highly proliferative breast cancer cells, where it curbs accumulation of double‐stranded RNAs (dsRNAs) and consequent induction of interferon responses and apoptosis. In contrast to other mammalian Argonaute protein family members with primarily cytoplasmic functions, AGO1x exhibits nuclear localization in the vicinity of nucleoli. We identify AGO1x interaction with the polyribonucleotide nucleotidyltransferase 1 (PNPT1) and show that the depletion of this protein further augments dsRNA accumulation. Our study thus uncovers a novel function of an Argonaute protein in buffering the endogenous dsRNA‐induced interferon responses, different than the canonical function of AGO proteins in the miRNA effector pathway. As AGO1x expression is tightly linked to breast cancer cell proliferation, our study thus suggests a new direction for limiting tumor growth. Synopsis: Protein levels of AGO1x, a conserved translational readthrough isoform of AGO1, are strongly correlated with breast cancer proliferation markers, indicating a potential link to tumor progression. Here, AGO1x is found to promote cancer cell proliferation by preventing dsRNA‐induced interferon signaling. AGO1x is expressed in breast cancer tissue and cell lines. AGO1x localizes predominantly to the nucleus, in the vicinity of nucleoli. AGO1x interacts with dsRNA‐processing proteins such as PNPT1. Genetic deletion of AGO1x causes dsRNA accumulation, and increased interferon signaling and apoptosis. Abstract : AGO1x, a translational readthrough isoform of Argonaute 1, localizes to the nucleus and interacts with proteins involved in dsRNA processing, promoting dsRNA clearance.